Adoption Choice of Risk Management Tools in Agricultural Production under Climate Change - Nsikak-Abasi Etim; Dorothy Thompson; NseAbasi Etim (Newinera Publisher, 2020)
The long term impact of climate change is likely to affect food security and therefore prompts the agricultural sector to be more resilient to production and market risk, and uncertainties caused by these changes in climate. Choosing from a wide range of risk management tools can help farmers manage uncertainties and adapt to climate change. However, the choice of adoption of these risk management tools are greatly influenced by a number of factors. An empirical study was conducted to estimate the factors influencing the adoption choice of agricultural risk management tools by farmers in Akwa Ibom State, Nigeria. Multistage sampling procedure was employed to select the representative farmers for the study. Information were elicited from farmers using questionnaires. Factors influencing the adoption of crop diversification, insurance and contract farming were analyzed using multinomial logit approach. Empirical results revealed that the decision to adopt crop diversification and insurance were inversely and significantly affected by age of the farmers. Results further showed that farmers decision to adopt crop diversification and contract farming as risk management tools were positively and significantly influenced by the size of farmland at (p<0.05). Findings also showed that access to weather information and frequency of extension contact significantly influenced farmers decision to adopt crop insurance and crop diversification respectively at 10% level. Result indicates that farmers decision to adopt crop diversification as a risk management tool was positively affected by frequency of extension contact. Promoting efficient and effective extension service delivery, access to weather and climate information and human capital development would be sensible policy options.